Expanding the Chondroitin Sulfate Glycoproteome — But How Far? - Noborn, Fredrik; Nikpour, Mahnaz; Persson, Andrea; Nilsson, Jonas; Larson, Göran (Frontiers in Cell and Developmental Biology, 2021)
Chondroitin sulfate proteoglycans (CSPGs) are found at cell surfaces and in connective tissues, where they interact with a multitude of proteins involved in various pathophysiological processes. From a methodological perspective, the identification of CSPGs is challenging, as the identification requires the combined sequencing of specific core proteins, together with the characterization of the CS polysaccharide modification(s). According to the current notion of CSPGs, they are often considered in relation to a functional role in which a given proteoglycan regulates a specific function in cellular physiology. Recent advances in glycoproteomic methods have, however, enabled the identification of numerous novel chondroitin sulfate core proteins, and their glycosaminoglycan attachment sites, in humans and in various animal models. In addition, these methods have revealed unexpected structural complexity even in the linkage regions. These findings indicate that the number and structural complexity of CSPGs are much greater than previously perceived. In light of these findings, the prospect of finding additional CSPGs, using improved methods for structural and functional characterizations, and studying novel sample matrices in humans and in animal models is discussed. Further, as many of the novel CSPGs are found in low abundance and with not yet assigned functions, these findings may challenge the traditional notion of defining proteoglycans. Therefore, the concept of proteoglycans is considered, discussing whether “a proteoglycan” should be defined mainly on the basis of an assigned function or on the structural evidence of its existence.